Analysis of the content of preparatory school biology books in light of pivotal thinking skills - et. al., Prof. Dr. Haider Mesir Hamdallah, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aims to analyze the content of biology books for the preparatory stage in the light of pivotal thinking skills for the academic year (2021/2020). The research problem was identified in the following questionsWhat are the pivotal thinking skills that should be included in the content of biology books for the preparatory stage? And what is the percentage?What are the main and subsidiary pivotal thinking skills included in the content of biology books for the preparatory stage? And what is the percentage?The pivotal thinking skills in the content of biology books for the preparatory stage include eight main skills (remembering, information gathering, concentration, organization, analysis, generation, integration, evaluation) and twenty-one sub-skills: (defining problems, setting goals, observation, formulating questions, coding, recalling, comparing, categorizing, arranging, representing, defining features and components, defining patterns and relationships, defining main ideas, identifying errors, inference, prediction, expansion, summarizing, reconstructing, building standards, validation, and according to the arbitrators’ expectations for the percentages of including pivotal thinking skills in the content of biology books for the preparatory stage, the percentages for these skills were as follows: Organizing skill obtained (20%), analysis (20%), focus (15%), information gathering (10%) and remembering (10%).Integration (10%), Obstetrics (10%) and evaluation (5%). In order to verify the inclusion of pivotal thinking skills in the content of biology books, the researcher prepared a list of pivotal thinking skills, which consisted of (8) main skills and (21) sub-skills, and the validity and reliability were verified after being presented to a group of experts and arbitrators, the researcher carried out the analysis process for the three targeted books for the preparatory stage, the results were recorded by means of repetitions and percentages, using the descriptive analytical approach, and based on the unity of the explicit idea, where the stability of the analysis was confirmed by agreement of the researcher with external analysts and the researcher himself over time, the researcher prepared a test for the pivotal thinking skills, the eight main and the twenty-first sub-aforementioned, and to verify the validity of the test in its initial form, it was presented to a group of arbitrators. The clarity of its items and their relevance to students were ensured, and the psychometric properties of the test were confirmed by calculating the internal consistency of the items and calculating the discrimination coefficient, and the difficulty coefficient of the items on a sample of students consisting of (120) male and female students, and the stability was calculated by the Kewder-Richardson equation 20, so the test became ready for the final application, and it consisted of (30) items, the test was applied at the end of the first course of the academic year (2020-2021) on a random sample of (300) male and female students from the sixth preparatory students, distributed over (5) schools from the morning schools for the preparatory stage in the center of Kirkuk governorate, and after the data was collected and processed using the statistical package Spss, and some statistical methods were used, including: Holstey equation and percentages, t-test for one sample and t-test for two independent samples, the researcher used Microsoft Office Excel 2010, objective item difficulty and ease coefficient, item discrimination equation, efficacy equation of wrong alternatives, Point-Basierial correlation coefficient, Keuder-Richardson equation 20.The percentages of pivotal thinking skills in the biology book for the fourth preparatory grade are as follows:Where the skill of organization got a percentage of (22.85), followed by the skill of concentration (20.38), analysis skill by (16.80), collecting information by (13.77), the skill of generation (12.76), the skill of integration by (4.95), and the evaluation skill by (4.64). ), and finally the memory skill with a percentage of (3.85).